Glia and Neural Stem and Progenitor Cells of the Healthy and Ischemic Brain: The Workplace for the Wnt Signaling Pathway - Knotek, Tomas; Janeckova, Lucie; Kriska, Jan; Korinek, Vladimir; Anderova, Miroslava (Genes, 2020)
Wnt signaling plays an important role in the self-renewal, fate-commitment and survival of the neural stem/progenitor cells (NS/PCs) of the adult central nervous system (CNS). Ischemic stroke impairs the proper functioning of the CNS and, therefore, active Wnt signaling may prevent, ameliorate, or even reverse the negative effects of ischemic brain injury. In this review, we provide the current knowledge of Wnt signaling in the adult CNS, its status in diverse cell types, and the Wnt pathway's impact on the properties of NS/PCs and glial cells in the context of ischemic injury. Finally, we summarize promising strategies that might be considered for stroke therapy, and we outline possible future directions of the field.
Keywords: dospělí; Animals; Neurogenesis; Ischemic Attack, Transient; Adult; neurogeneze; Health; cílená molekulární terapie; buněčná diferenciace; lidé; neuroglie; Neural Stem Cells; zdraví; mozek; ischemie mozku; Wnt Signaling Pathway; nervové kmenové buňky; tranzitorní ischemická ataka; Brain; signální dráha Wnt; Brain Ischemia; Neuroglia; Cell Differentiation; zvířata; Molecular Targeted Therapy; Humans